PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP VOLUME PENJUALAN PT. LESTARI ALAM - Rintan Saragih (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
Marketing strategy is one way for companies to survive, earn profits, strengthen the company's position and develop the company in the face of competition. The marketing strategy that the company can do in facing the competition is through the activities of determining the selling price, promotion and brand image of the company. The test results that have been obtained from the results of multiple linear regression analysis show that brand image has a dominant relationship to increasing sales volume. Partial hypothesis testing (t-test) for brand image variables and price in accordance with the test requirements obtained that there is a positive and significant effect on sales volume, while the promotion variable) has no and no significant effect on sales volume. Simultaneous hypothesis testing (F-test) variable brand image, price), and promotion) simultaneously (simultaneously) have a positive and significant effect on sales volume. The coefficient of determination using the Adjusted R-Square value shows that the contribution of the independent variables, including brand image, price, and promotion in influencing customer loyalty is 73.9%.